2010
DOI: 10.1016/j.cub.2010.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Onset of Sexual Maturation and Mating Behavior by Melanocortin Receptor 4 Polymorphisms

Abstract: Polymorphisms in reproductive strategies are among the most extreme and complex in nature. A prominent example is male body size and the correlated reproductive strategies in some species of platyfish and swordtails of the genus Xiphophorus. This polymorphism is controlled by a single Mendelian locus (P) that determines the onset of sexual maturity of males. Because males cease growth after reaching puberty, this results in a marked size polymorphism. The different male size classes show pronounced behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
116
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 40 publications
2
116
1
2
Order By: Relevance
“…Defective copies have lost their capability for signal transduction because microdeletions have removed important cysteine residues from the carboxy-terminal region of the receptor. Such defective copies were detected only in males, being located on the Y chromosome (Lampert et al 2010). Copy-number variation correlating with mc4r expression levels was observed for the defective mc4r copies in males: the highest copy-number and expression levels were found in large late-maturing males, while small early maturing males showed low copy number and low levels of expression.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Defective copies have lost their capability for signal transduction because microdeletions have removed important cysteine residues from the carboxy-terminal region of the receptor. Such defective copies were detected only in males, being located on the Y chromosome (Lampert et al 2010). Copy-number variation correlating with mc4r expression levels was observed for the defective mc4r copies in males: the highest copy-number and expression levels were found in large late-maturing males, while small early maturing males showed low copy number and low levels of expression.…”
mentioning
confidence: 91%
“…In contrast, X. nigrensis and X. multilineatus, two swordtail species distantly related to X. maculatus within the genus Xiphophorus (Kang et al 2013), present only three major P-determined male phenotypes (small/ early maturing, large/late-maturing, and one intermediate phenotype). In these species, it has been shown that puberty onset, body size, and reproductive behavior are modulated by sequence polymorphism and gene copy-number variation affecting the type 4 receptor for melanocortin hormones, Mc4r (Lampert et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the MC4R was found to be highly expressed in gonads of several fi sh, such as goldfi sh [42], Ya-fi sh [30], and snakeskin gourami [45]. In addition, some previous studies revealed that MC4R copies located on the sex chromosomes participate in the functional modulation of onset of sexual maturity in both male and female swordtails and platyfi sh, suggesting the potential participation of MC4R in the regulation of reproduction [31,46]. Hence, understanding how MC4R mediates the reproductive function in economically important species is important for artifi cial breeding.…”
Section: Dasyatis Akajeimentioning
confidence: 98%
“…Male body size depends on a Y-linked polymorphism that induces sexual maturation and dramatically slows growth [11]. Males that mature at a small size obtain fertilizations by coercively sneaking copulations while males of large and intermediate size court females but rarely sneak [12].…”
Section: Introductionmentioning
confidence: 99%